2010
DOI: 10.1103/physrevb.82.184425
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic spectrum of the two-dimensional antiferromagnetLa2CoO4studied by inelastic neutron scattering

Abstract: We report measurements of the magnetic excitation spectrum of the layered antiferromagnet La2CoO4 by time-of-flight neutron inelastic scattering. In the energy range probed in our experiments (0-250 meV) the magnetic spectrum consists of spin-wave modes with strong in-plane dispersion extending up to 60 meV, and a nearly dispersionless peak at 190 meV. The spin-wave modes exhibit a small (∼ 1 meV) dispersion along the magnetic zone boundary. We show that the magnetic spectrum can be described very well by a mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 27 publications
6
42
0
Order By: Relevance
“…This is inconsistent with the stripe-free model, which requires the fully gapped La 2 CoO 4 -type magnon spectrum in order to produce the waist and upper part of the hourglass. In addition, the magnon spectrum of Néel-ordered La 2 CoO 4 is isotropic until the spectrum approaches the zone boundary at high energies23, and therefore cannot reproduce the observed tetragonal anisotropy and 45° rotation of the intensity maxima relative to the fourfold pattern below the waist of the hourglass12.…”
Section: Discussionmentioning
confidence: 99%
“…This is inconsistent with the stripe-free model, which requires the fully gapped La 2 CoO 4 -type magnon spectrum in order to produce the waist and upper part of the hourglass. In addition, the magnon spectrum of Néel-ordered La 2 CoO 4 is isotropic until the spectrum approaches the zone boundary at high energies23, and therefore cannot reproduce the observed tetragonal anisotropy and 45° rotation of the intensity maxima relative to the fourfold pattern below the waist of the hourglass12.…”
Section: Discussionmentioning
confidence: 99%
“…Here, the double exchange interactions between Co 3+ and Co 4+ are playing an important role in controlling the magnetic/spin-state transitions. Also, the layered cobaltites La 2−x Sr x CoO 4 (containing both Co 2+ and Co 3+ ) are very interesting to understand the role of different spin as well as valence states of Co ions in controlling the magnetic, transport and electronic properties [35][36][37][38][39][40][41]. For example, it has been reported that the Co 2+ present mostly in HS state, whereas different spin-states are possible in Co 3+ [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic excitations in La 2−x Sr x CoO 4 were studied for pure La 2 CoO 4 [154], for half-doped La 1.5 Sr 0.5 CoO 4 [138,147,148] and more recently also for La 1.67 Sr 0.33 CoO 4 [152]. The magnon dispersion in the pure and in the half-doped material can be well described by linear spin-wave theory and thus allows one to determine the magnetic interaction between two neighboring Co 2+ moments J nn and that between two Co 2+ moments connected by an intermediate non-magnetic Co 3+ , J ′′ see Fig.…”
Section: (C)mentioning
confidence: 99%